Opting for predicating a theme in translation – a dilemma - Daniela Corina Ionescu (Bucharest Working Papers in Linguistics, 2009)
Predicating the theme in a sentence/text regards the organization of information structure (balance between given and new information units) according to the author’s intention and textual (writing) skills; to transpose this balance in translation is the translator’s job, not always devoid of difficulties or hesitations. Obviously, the target language is constantly “revised” for checking the equivalent devices in theme predicating strategies. The present paper discusses a specific text and its information structure from the viewpoint of dynamic equivalence.